Satisfaction Level of Farmers Regarding e-Choupal Services - Raghvanshi, Tushar; Awasthi, Nimisha ,; Singh, A K; Singh, Manish (Indian Journal of Extension Education, 2020)
e-Choupal tackles the challenges posed by Indian Agriculture, characterized by fragmented farms, weak infrastructure and the involvement of intermediaries. The programme installs computers with Internet access in rural areas of India to offer farmers up-to-date marketing and agricultural information. ITC Limited kiosk with Internet access is run by a sanchalak- a trained farmer. Being one among the numerous private ICT initiatives need to be studied in detail owing to its success and to know about satisfaction level of users for various services provided by e-choupal. Multistage Purposive random sampling technique was adopted to carry out the research. Two villages out of two selected block were randomly selected, and from each selected village 30 e-Choupal users selected randomly for data collection. Results revealed that more than seventy five percent respondents ˜Strongly agree over the bench mark price set by ITC for crops procurement is comparatively higher than any other agencies while, more than 65% respondents were highly satisfied with marketing of crops. Majority were medium level satisfied with supply of proper inputs by e- choupal.